Pengaruh Gaya Kepemimpinan dan Disiplin Kerja terhadap Kinerja Pegawai Kantor Dinas Perpustakaan dan Kearsipan Kabupaten Musi Banyuasin - Hendry Wijaya; Tri Nusi Marcindo Saputra; Rully Alamsyah (MAMEN: Jurnal Manajemen, 2024)
The Influence of Leadership Style and Work Discipline on the Performance of Library and Archives Service Employees in Musi Banyuasin Regency, South Sumatra Province. The sample uses the Slovin formula. The data collection method used was by giving questionnaires to employees of the Musi Banyuasin Regency Library and Archives Service. Data were analyzed using the Quantitative Method, namely using validity tests, reliability tests, classical assumption tests, regression analysis, correlation analysis, determination analysis and t tests with the help of SPSS 22.0 for Windows software. The results of the research show that there is an influence of leadership style and work discipline on employee performance at the Musi Banyuasin Regency Library and Archives Office. The coefficients for leadership style and work discipline are positive, indicating a unidirectional relationship, in other words, leadership style and work discipline will have a significant effect on performance. The relationship between leadership style and work discipline on employee performance shows a moderate relationship (R=0.506). The coefficient of determination or R square number is 0.256, which means that 25.6 percent of employee performance variables are influenced by leadership style and work discipline.